A hint of the summery goodness of green grass: a look at English descriptors in tasting notes - Belén López Arroyo; Lucia Sanz-Valdivieso (Revista de Lingüística y Lenguas Aplicadas)
Tasting descriptors, which are common terms used to describe a food product, play a significant role in tasting discourse and particularly in tasting notes. Although they have been the subject of a number of studies from different perspectives, none of them describe and classify descriptors from their form, function and combination in tasting notes in English. In this paper, we examine a corpus of tasting notes with the aim of 1. determining the positioning of English descriptors in relation to the keywords designating the tasting process; 2. scoping the depth of description, as indicated by the number of descriptors; 3. identifying if the descriptors are specific to a given aspect of the food product or are generic enough to be used to describe different aspects of it.; and 4. categorizing frequent semantic associative processed among descriptors and keywords. Our results will be a valuable resource for professionals, technical writers and students’ tasters in English.